2014
DOI: 10.1093/bja/aet469
|View full text |Cite
|
Sign up to set email alerts
|

Brain regional vulnerability to anaesthesia-induced neuroapoptosis shifts with age at exposure and extends into adulthood for some regions

Abstract: The present study confirms the findings of previous studies showing peak vulnerability to anaesthesia-induced neuronal cell death in the newborn forebrain. It also shows sustained susceptibility into adulthood in areas of continued neurogenesis, substantially expanding the previously observed age of vulnerability. The differential windows of vulnerability among brain regions, which closely follow regional peaks in neurogenesis, may explain the heightened vulnerability of the developing brain because of its inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 38 publications
2
58
0
1
Order By: Relevance
“…The hippocampus serves a crucial role in regulating the cognitive function (11). A previous study demonstrated that the hippocampus is vulnerable to adverse events, including hypoxemia, exposure to inhaled anesthetics and surgical trauma (12). Evidence from magnetic resonance imaging studies indicated that decreased hippocampal volume is significantly associated with mild cognitive impairment in various neuropsychiatric diseases (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…The hippocampus serves a crucial role in regulating the cognitive function (11). A previous study demonstrated that the hippocampus is vulnerable to adverse events, including hypoxemia, exposure to inhaled anesthetics and surgical trauma (12). Evidence from magnetic resonance imaging studies indicated that decreased hippocampal volume is significantly associated with mild cognitive impairment in various neuropsychiatric diseases (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to isoflurane, however, led to a dramatic increase in the number of caspase-3 immunoreactive cells in the dentate gyrus ( Fig.1), consistent with previous studies. 13,14 Moreover, quantification of caspase-3 immunolabeling in GFP-expressing cells revealed a five-fold increase in double-labeled cells relative to controls. Specifically, in 21-day-old control animals, 2.05±0.75% of GFPexpressing cells co-labeled with caspase-3, while 11.03±1.75% of cells in the P21 anesthesia group expressed caspase-3 ( Fig.1; P<0.001, t-test).…”
Section: Resultsmentioning
confidence: 98%
“…11,12 A second complicating factor is the potential for compensatory neurogenesis among certain neuronal populations sensitive to anesthesia-induced death. Specifically, we and others have recently demonstrated that hippocampal dentate granule cells are especially vulnerable to anesthesia-induced neurotoxicity in 21 day-old (P21) mice, 13,14,15 a brain maturational stage comparable to human infants. 16 Granule cells, however, are produced throughout life in animals and humans, 17 so it is conceivable that the dentate could regenerate lost cells.…”
Section: Introductionmentioning
confidence: 87%
“…In newborn mice, general anaesthesia with 1.5 Vol.% isoflurane has been found to cause a 4-11 fold increase of neuronal death in various brain regions, as compared to controls. [10,28,29] A 6-hour isoflurane exposure eliminates approximately 2% of cortical neurons [14]. Apoptosis appears to be the predominant mode of isoflurane-induced death, as evidenced by caspase-3 cleavage [10].…”
Section: Resultsmentioning
confidence: 99%